The Effect of Thin Capitalization Capital Intensity and Multinationality on Tax Avoidance with the Utilization of Tax Havens Countries as a Moderating Variable - Fitria, Zuhro Yatul; Seralurin, Yohanes C.; Patma, Kurniawan; Pattiasina, Victor (Sekolah Tinggi Ilmu Ekonomi AMM, 2024)
This research aims to examine the influence of thin capitalization, capital intensity, and multinationality on tax avoidance by using tax havens countries as a moderating variable. This research uses a sample of multinational companies in the manufacturing sector listed on the Indonesia Stock Exchange during the 2019-2022 period. The number of companies in the research sample was 32 companies over four years. The total research sample was 128 financial reports and annual reports. Data were analyzed using the Moderate Regression Analysis (MRA) method with the help of SPSS 26 software. The results of this research show that thin capitalization and multinationality have no effect on tax avoidance, while capital intensity has a significant negative effect on tax avoidance. The use of country tax havens strengthens the influence of thin capitalization and multinationality on tax avoidance. The use of country tax havens weakens the influence of thin capitalization and multinationality on tax avoidance.